Experimental Quantification of the Variability of Mechanical Properties in 3D Printed Continuous Fiber Composites - Clarissa Becker; Hannes Oberlercher; Rosmarie Brigitte Heim; Günter Wuzella; Lisa-Marie Faller; Franz Oswald Riemelmoser; Pascal Nicolay; Frédéric Druesne (Applied Sciences, 2021)
The material properties of 3D printed continuous fiber composites have been studied many times in the last years. However, only a minimal number of samples were used to determine the properties in each of the reported studies. Moreover, reported results can hardly be compared due to different sample geometries. Consequently, the variability of the mechanical properties (from one sample to the other) is a crucial parameter that has not been well quantified yet. In the present work, the flexural properties of 3D printed continuous carbon fiber/nylon composite specimens were experimentally quantified, using batches of 15 test specimens. In order to account for the possible influence of the quality of the prepreg filaments on the observed variability, three different filament rolls were used to manufacture the different batches. Also, two configurations were tested, with a fiber direction parallel (longitudinal) or perpendicular (transverse) to the main axis of the specimens. The results show moderate to high variabilities of the flexural modulus, flexural strength and maximum strain. The coefficient of variation was more than twice as high in the transverse case as in the longitudinal case.